Well-being Messaging for Mammalian Milks: A Scoping Review - Moradi S; Hort J (Frontiers Media S.A., 2021)
Having a holistic understanding of research on well-being messaging for milk is vital to allow the optimal communication of the association between milk consumption and various nutritional, physical, and psychological benefits to the consumer. This work is a unique interdisciplinary, scoping review of existing research on well-being messaging for milk. Well-being messages are ways to communicate the broad well-being benefits of specific products to the consumer through information on food content or statements that link a product with favourable components, functions, or well-being outcomes. Leveraging this broad definition, and by proposing a guiding theoretical model that considers well-being messaging as a form of communication, milk well-being messaging literature has been mapped across time, geographical locations, disciplines, and product types. Two hundred forty-six were records included in this review, of which 177 were empirical studies. Studies were disseminated between 1954 and 2019, with 54.9% published after 2011. Food, Agriculture, and Biological Sciences (N = 109), Nutrition and Dietetics (N = 78), and Medicine, Public Health, and Health Professions (N = 69) disciplines have attracted the most publications, with numbers generally increasing in most recent years. The majority of included non-empirical records (69.6%) provide lists of commercially available products carrying well-being messaging and/or regulations on the use of particular well-being messages for milk according to various legislative authorities. Most of the empirical studies were conducted in North America (N = 71), West Europe (N = 52), and Oceania (N = 22), and on plain (i.e., unflavoured) milk (N = 152). Whereas, most studied elements of well-being messaging for milk across time, i.e., message (N = 169), product (N = 141), receiver (N = 101), and context (N = 72) have seen an increasing number of studies in recent years; sender (N = 51) and medium (N = 27) have been even less studied in the past four years. A more detailed analysis of research trends in each element of well-being messaging is reported. The research highlights immediate and strategic knowledge gaps that need further attention from researchers and/or policymakers in order to improve the "messaging" of well-being benefits of milk consumption to the consumer.
Keywords: food label; health claim; health communication; milk; scoping review; well-being; well-being messaging